Impact of Parent Interest in Mathematics and Students Mathematics Interest on Student Mathematics Achievement - Boateng, Francis Ohene; Bandoh, Sampson Owusu; Kwarteng, Sarah; Lotey, Ebenezer Kwesi (Department of Mathematics Education University of Muhammadiyah Malang, 2024)
A student's academic and cognitive development is greatly influenced by their mathematics education, and the importance of parental participation in promoting this interest cannot be estimated. The study aims to evaluate the impact of parental interest in mathematics and student’s mathematics interest on students’ mathematics achievement. The study employed quantitative research method with the used of structured questionnaire for collecting data. The sample of the study comprised of 200 first-year students from four selected senior high school in Ghana-Kumasi. The study findings revealed that, parent interest and student interest in mathematics had a statistically significant direct positive impact on students’ mathematics achievement. Moreover, there relationship between parental interest and students’ interest in mathematics had a positive effect and was statistically significant.